Communication Roles of Languages in Multilingual Societies - Nida, Eugene Albert (The Bible translator, 1971)
Communication Roles of Languages in Multilingual Societies is published in TBT because it offers translators some valuable insights in the understanding of the different functions which different languages perform within societies. Bible translators are increasingly asking themselves if the languages they work in might not be giving way to the pressures of some more widely used languages. Nida and Wonderly provide us with ways of assessing the various jobs competing languages are called on to perform. A careful study of this article should enable a translator to evaluate the faces of multilingualism more accurately and to assess the nature of a changing linguistic scene.A shorter version of this article was first published in Language Use and Social Change: problems of multilingualism with special reference to Eastern Africa: studies presented and discussed at the ninth International African Seminar at University College, Dar es Salaam, 1968, edited, with an Introduction by W. H. Whiteley. London: Oxford University Press for International African Institute, 1971. Pp. vi, 406, £3.